IMPLEMENTASI INOVASI WEBSITE AI PAK SAMSON DALAM MENINGKATKAN EFEKTIVITAS LAYANAN DI KB SAMSAT PONOROGO - Martika Fatmawati; Cellin Avryanda; Dindy Aprilia Nur Halisa; Dodhi Nugraha; Yusuf Setio Budi; Vicky Husada; Siti Chamidah (Jurnal Pijar, 2026)
This study aims to analyse the implementation of the PAK SAMSON (Ponorogo Online Samsat Communication Service) website innovation in improving the effectiveness of public services at the Ponorogo Samsat Office. This digital transformation is an effort to overcome the obstacles of complex bureaucratic procedures and physical queues that hinder time and cost efficiency for taxpayers. This study uses a qualitative descriptive approach with data collection techniques through direct observation, in-depth interviews, and analysis of supporting documents. The results show that the implementation of Website PAK SAMSON has successfully integrated e-government principles through strategic features such as an AI-based automatic tax calculator and an online vehicle sale report blocking service with an accuracy rate of 95%. Operationally, this innovation has reduced service time from 30-60 minutes to only 1-3 minutes and reduced physical queues by 20-30%. The ease of accessibility through an intuitive interface and multilingual AI chatbot features has been proven to increase taxpayer independence. The implications of this research show that the integration of digital technology supported by transparent governance can significantly improve institutional accountability and public satisfaction.